The Clergy during the Fourth Crusade as Portrayed in Robert of Clari’s Chronicle - Pentek, Zdzisław (Studia Ceranea, 2024)
This article deals with the view of clerical participants in the Fourth Crusade found in Robert of Clari’s Old-French chronicle La conquête de Constantinople. The author has analysed the chronicler’s references to members of the clergy, specifying three different types of clergymen who took part in the expedition to Constantinople.